An electrically reversible switchable surface to control and study early bacterial adhesion dynamics in real-time - Pranzetti, Alice (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.